Transgender health issues addressed in research on telehealth use: a scoping review - Gahbauer, Susanne; Haluza, Daniela (Frontiers in Sociology, 2024)
Telehealth is a valuable tool for reminding transgender-persons to undergo HIV testing, hormone injections, and voice training. Despite increased awareness of the unique health needs of transgender-individuals in recent years, effectively addressing their concerns remains challenging. The COVID-19 pandemic has negatively affected socioeconomic status, mental health, and access to gender-affirming treatment. To better understand how individuals and their specific health issues are addressed in telehealth solutions, we conducted a scoping review using PubMed and Scopus, spanning from 2000 to 2021. We screened eligible articles following the PRISMA checklist, extracted the data, and performed a thematic analysis of 100 reports. For control purposes, we double-checked the ratings during the screening and coding. Our results show that telehealth is primarily used for healthcare access, sexual and reproductive health, and mental health. Since 2020, the overall number of publications has greatly increased, with only nine reports explicitly referring to COVID-19-related challenges. The latter relate exclusively to clinical purposes such as healthcare access. We found that transgender-women were researched more often than transgender-men, particularly in the field of sexual and reproductive health research. Some studies included groups other than transgender-persons, such as parents or clinicians, who might be relevant for advancing telehealth use. The review’s findings highlight the need for more research that considers the diversity of transgender-groups and the adapted use of diverse technological tools beyond pandemics and public health crises.